Perencanaan Keuangan Keluarga Menuju Kemandirian Ekonomi di Desa Karang Anyar Kecamatan Beringin Kabupaten Deli Serdang - Dina Rosmaneliana; Rebecca Evadine; Nikous Soter Sihombing; Monetarist Butar Butar; Togar Timoteus Gultom; Petrus Loo (Universitas Methodist Indonesia, 2025)
Financial planning is an essential foundation to support household economic stability, resilience, and long-term welfare. This community service program aims to provide education, training, and practical guidance on family financial planning for community members, especially housewives. The activity includes knowledge enhancement regarding budgeting, the 50-30-20 allocation principle, debt management, savings and investment strategies, emergency funds, and financial protection. The program was carried out through workshops, interactive counseling, and practice sessions using simple financial tools. The results show that participants experienced an increase in understanding and skills in managing household finances, were able to create monthly budgets, identify financial leaks, and formulate savings and investment plans. This community service contributes to strengthening family financial independence toward sustainable household welfare.